Determination of stopping distance for low CC motorcycles with antilock braking - Fauziana Lamin,; Zarir Hafiz Zulkipli,; Azhar Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Motorcycles are among the favorite transportation preferred by Malaysians. Almost half of the vehicles registered in Malaysia are motorcycles. This is due to the price affordability and size, where almost 80% of the motorcycles owned are categorized under engine capacity below 250 cc. Similar to other Southeast Asia countries, motorcyclists remain the highest contributor to road traffic fatalities and injuries in Malaysia. The New Car Assessment Program (NCAP), has elevated the importance of safety technology in passenger cars such as anti-lock braking system (ABS) and autonomous emergency braking (AEB) in order to protect the occupants. However, the limitation of space and power requirements in two-wheel motorcycles deferred the technology implementation. Previous studies have attempted to study the effectiveness of ABS for motorcycles with 250 cc and above. Focusing on the low cc motorcycle of less than 250 cc, this paper compares motorcycle braking distance and rider stability between motorcycles with ABS and motorcycles without ABS during dry and wet conditions. The braking distance produced by ABS is reduced by 50% and 12% in dry and wet conditions respectively. In addition, motorcycles with ABS were tested at higher speeds of 50 km/h. ABS motorcycles shows consistent data for a series of tests. This finding demonstrates the effectiveness of ABS in improving braking performance for low cc motorcycles.